Correlation of polymerase chain reaction results with hematocrit levels and platelet counts in dengue patients in Batam City - Simangunsong, Kristina; Nurhayati, Betty; Hayati, Eem; Merdekawati, Fusvita (Current Biomedicine, 2025)
Background Dengue hemorrhagic fever (DHF) is a viral disease transmitted by Aedes aegypti mosquitoes, posing global public health challenge. The Riau Islands Province has the highest incidence of DHF in Indonesia. Objective This study aimed to investigate the relationship between hematocrit and platelet levels with the cycle threshold (Ct) values of polymerase chain reaction (PCR) results in DHF cases in Batam City, Riau Islands Province. Methods A descriptive correlation study was conducted using data from 102 patients infected with the dengue virus. Hematocrit and platelet counts were measured using a hematology analyzer, while Ct values for DENV1, DENV2, DENV3, and DENV4 were obtained through real-time qRT-PCR. Pearson's correlation test was employed to analyze the relationship between these variables. Results The study found no significant gender difference in DHF incidence (males: 50%, females: 50%). The highest prevalence was observed in the 6–11 years age group (44.1%), followed by the 12–18 years group (25.5%), the >18 years group (24.5%), and the 1–5 years group (11.8%). DENV3 was identified as the dominant serotype. No statistically significant correlation was found between Ct values and hematocrit (p = 0.607) or platelet counts (p = 0.323). Conclusion DHF cases in this study showed no gender disparity, with the most affected group being children aged 6–11 years, and DENV3 was the prevalent serotype. Ct values did not show a statistically significant correlation with hematocrit levels or platelet counts, suggesting that these hematological parameters may not predict viral load in DHF cases.